Probing Corticospinal Recruitment Patterns and Functional Synergies with Transcranial Magnetic Stimulation - Mathew, James; Kübler, Angelika; Bauer, Robert; Gharabaghi, Alireza (Frontiers in Cellular Neuroscience, 2016)
Background: On the one hand, stimulating the motor cortex at different spots may activate the same muscle and result in a muscle-specific cortical map. Maps of different muscles, which are functionally coupled, may present with a large overlap but may also show a relevant variability. On the other hand, stimulation of the motor cortex at one spot with different stimulation intensities results in a characteristic input-output (IO) curve for one specific muscle but may simultaneously also activate different, functionally coupled muscles. A comparison of the cortical map overlap of synergistic muscles and their input-out curves has not yet been carried out. Objective: The aim of this study was to probe functional synergies of forearm muscles with transcranial magnetic stimulation by harnessing the convergence and divergence of the corticospinal output. Methods: We acquired bi-hemispheric cortical maps and IO curves of the extensor carpi ulnaris, extensor carpi radialis and extensor digitorum communis muscles by subjecting eleven healthy subjects to both monophasic and biphasic pulse waveforms. Results: The degree of synergy between pairs of forearm muscles was captured by the overlap of the cortical motor maps and the respective IO curves which were influenced by the pulse waveform. Monophasic and biphasic stimulation were particularly suitable for disentangling synergistic muscles in the right and left hemisphere, respectively. Conclusion: Combining IO curves and different pulse waveforms may provide complementary information on neural circuit dynamics and corticospinal recruitment patterns of synergistic muscles and their neuroplastic modulation.